(untitled) (מכאן, 2008)
The goal of this article is to introduce a new form of the "Talush" (uprooted) as it appears in modern Hebrew literature in the works of Israeli writers of the 40s and 50s. the new character, called in this article "Ha’talush-Ha’sabra", is a product of an oxymoronic union of the character of the Sabra and the talush. Both characters represent two opposites of the Jewish existence — the Sabra and the uprooted Jew. Ha’talush-Ha’sabra character creates a new model in which "rootless- ness" is viewed as a transition period from which one can leave and rebuild oneself, but is also based on previous models and t its of the Talush character, like the twofold character of this new model of the Talush, the writers had two major roles in creating it: On one hand, they viewed rootless-ness as an essential experience in reshaping the young hero. On the other hand, they used it to criticize and illuminate the defects of the society as well as to present the youths as damaged by the society which raised them. This research examines the character of Ha’talush-Ha’sabra in the following works: S. Yizhar — Misholim Ba’sadot (Trials in the Fields, 1938), Moshe Shamir — Hue Halakh Ba’sadot (He Walked in the Fields, 1948) and Hanoch Bartov, Ha’kheshbon Veha’nefesh (Soul and Reckoning, 1953).